The Effectiveness of Combined Cognitive-Behavioral and Neurorehabilitation Interventions on Improving Social Skills in Children with Autism Spectrum Disorder (Scientific Journal of Research Studies in Future Psychology, 2025)
Autism Spectrum Disorder (ASD) is one of the most prevalent neurodevelopmental disorders, characterized by deficits in social skills, communication, and repetitive behaviors. Social challenges in children with ASD not only affect their academic and family functioning but also significantly limit their quality of life and social participation. In recent years, combined intervention approaches that integrate cognitive-behavioral therapy (CBT) with neurorehabilitation techniques have gained growing attention in psychology and clinical neuroscience. The present study aims to evaluate the effectiveness of combined CBT and neurorehabilitation interventions in improving social skills among children with ASD. This research employed a systematic review of clinical and quasi-experimental studies published over the past five years, comparing the effectiveness of single-modality and combined interventions. Findings indicate that simultaneous application of CBT and neurorehabilitation methods—including neurofeedback training, non-invasive brain stimulation, and cognitive rehabilitation exercises—led to significant improvements in communication skills, emotional regulation, and social interactions. These findings suggest that combined approaches may provide an innovative framework for enhancing clinical interventions in autism. Ultimately, the integration of multidimensional treatment modalities offers more sustainable and practical improvements in the social skills of children with ASD.